2013
DOI: 10.4304/jltr.4.3.605-610
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Use of Translation as a Learning Strategy in EFL Classroom

Abstract: Abstract-Translation has long played a controversial role in English teaching and learning. It has been largely ignored as a valid activity for language practice and improvement. On account of this matter, although, most language educators are completely against the use of translation in language classrooms, nowadays, this perspective is changing and more and more professionals have believed the facilitating role of the first language in ELT. On the basis of this matter, this issue has been discussed in applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 12 publications
8
35
0
Order By: Relevance
“…The result is consistent with the study conducted by Karimian and Talebinejad (2013) who reported that the use of direct translation of grammatical terms from the mother tongue could help to clarify the rules of the grammatical parts. The Persian participants in their study needed the security of their mother tongue to lower their anxiety level when learning English.…”
Section: Gema Online ® Journal Of Language Studiessupporting
confidence: 92%
See 3 more Smart Citations
“…The result is consistent with the study conducted by Karimian and Talebinejad (2013) who reported that the use of direct translation of grammatical terms from the mother tongue could help to clarify the rules of the grammatical parts. The Persian participants in their study needed the security of their mother tongue to lower their anxiety level when learning English.…”
Section: Gema Online ® Journal Of Language Studiessupporting
confidence: 92%
“…This result is similar to Karimian and Talebinejad's (2013) study in which the participants gathered some information in their first language (Persian) and translated it to the target language (English) to write a composition. When the participants could not find the English equivalent of the words during the writing process, they had to look up the words in the Persian-English dictionary.…”
Section: Gema Online ® Journal Of Language Studiessupporting
confidence: 81%
See 2 more Smart Citations
“…In fact, Karimian and Branch (2013) recognizes that "the use of translation can increase our sense of security to learn what we do not know" (p. 607), a valid statement applicable to this research study because learners were encouraged to deal with authentic literary language for the first time in their lives. In this sense, learners informed that they sometimes had to look up words in the dictionary to clarify understanding.…”
Section: Translating Was Used When Reading Authentic Textsmentioning
confidence: 99%